Temporal changes in characteristics, incidence, and mortality in patients undergoing surgical intervention for mitral stenosis - Hans T. Due; Jeppe K. Petersen; Daniel E. Meulengracht; Morten H. Smerup; Michael R. Schmidt; Lars Køber; Emil Fosbøl; Lauge Østergaard (Scientific Reports, 2024)
Abstract To examine temporal changes in patient characteristics, the incidence rate of surgical intervention, and the three-year mortality rate for patients undergoing surgical intervention for mitral valve stenosis (MS) from 2001 to 2021 in Denmark. Utilizing Danish nationwide registries, we identified all adult patients undergoing first-time surgical intervention for MS (2001–2021). Temporal changes in the incidence rate of surgical intervention across calendar periods were investigated (2001–2005, 2006–2010, 2011–2015, and 2016–2021). Using Kaplan-Meier estimates, we computed temporal changes in three-year all-cause mortality across calendar periods. With multivariable Cox regression analysis, we assessed the adjusted rates of mortality. We included 256 patients (median age 60.3 years, 31.3% males). A stepwise decrease in the burden of chronic heart failure was identified (2001–2005: 54%, and 2016–2021: 20%, p-value < 0.001 for trend), while the burden of atrial fibrillation seemed stable (2001–2005: 51%, and 2016–2021: 46%, p-value = 0.27 for trend). The proportion of patients with rheumatic MS was 64% in 2001–2005 and 33% in 2016–2021, p-value < 0.001 for trend. 28 patients (10.9%) had mitral valve surgery prior to the first-time surgical intervention for MS. A stepwise decrease in the incidence rate of surgical intervention was observed: 3.3 cases per million person-years in 2001–2005 and 2.2 in 2016–2021. The incidence of patients diagnosed with first-time MS remained stable over calendar periods (2001–2005: 54.5 incidences per million person-years, and 2016–2021: 41.9, p-value = 0.46 for trend). The in-hospital mortality was 8.6% and the three-year mortality after surgical discharge was 9.0%, and we found no difference over calendar periods in either crude estimates or adjusted analysis. From nationwide data across three decades, we identified that the incidence of surgical interventiondecreased significantly within the past 20 years, while all-cause mortality remained stable. The burden of heart failure decreased, while the burden of atrial fibrillation remained stable over the study period.